Entecavir treatment does not eliminate the risk of hepatocellular carcinoma in chronic hepatitis B: limited role for risk scores in Caucasians. Issue 8 (10th July 2014) - Arends, Pauline; Sonneveld, Milan J; Zoutendijk, Roeland; Carey, Ivana; Brown, Ashley; Fasano, Massimo; Mutimer, David; Deterding, Katja; Reijnders, Jurriën G P; Oo, Ye; Petersen, Jörg; van Bömmel, Florian; et al.
Abstract : Background: Hepatocellular carcinoma (HCC) risk-scores may predict HCC in Asian entecavir (ETV)-treated patients. We aimed to study risk factors and performance of risk scores during ETV treatment in an ethnically diverse Western population. Methods: We studied all HBV monoinfected patients treated with ETV from 11 European referral centres within the VIRGIL Network. Results: A total of 744 patients were included; 42% Caucasian, 29% Asian, 19% other, 10% unknown. At baseline, 164 patients (22%) had cirrhosis. During a median follow-up of 167 (IQR 82–212) weeks, 14 patients developed HCC of whom nine (64%) had cirrhosis at baseline. The 5-year cumulative incidence rate of HCC was 2.1% for non-cirrhotic and 10.9% for cirrhotic patients (p<0.001). HCC incidence was higher in older patients (p<0.001) and patients with lower baseline platelet counts (p=0.02). Twelve patients who developed HCC achieved virologic response (HBV DNA <80 IU/mL) before HCC. At baseline, higher CU-HCC and GAG-HCC, but not REACH-B scores were associated with development of HCC. Discriminatory performance of HCC risk scores was low, with sensitivity ranging from 18% to 73%, and c-statistics from 0.71 to 0.85. Performance was further reduced in Caucasians with c-statistics from 0.54 to 0.74. Predicted risk of HCC based on risk-scores declined during ETV therapy (all p<0.001), but predictive performances after 1 year were comparable to those at baseline. Conclusions: Cumulative incidence of HCC is low in patients treated with ETV, but ETV does not eliminate the risk of HCC. Discriminatory performance of HCC risk scores was limited, particularly in Caucasians, at baseline and during therapy.